Understanding Students’ Behavioral Intention to Adopt Blended Learning : Modified UTAUT Model - Shokeen, Anjali; Kumar, Ashish; Khanna, Swati (Prabandhan: Indian Journal of Management, 2023)
Purpose : The presented study explored the critical antecedents of blended learned adoption by students in India. It extended the unified theory of acceptance and use of technology (UTAUT) with attitude (ATT) and self-management of learned (SL) as additional constructs. Methodology : The proposed model was tested empirically using confirmatory factor analysis (CFA) and structural equation modeling (SEM). The data were collected through a questionnaire from 383 New Delhi, Indian students for a period from January 2020 to December 2021. Findings : The analysis of the data revealed that effort expectancy (EE), performance expectancy (PE), facilitating conditions (FC), and SL had significant positive effects on behavioral intention (BI) and ATT toward blended learning. The impact of socially influenced (SI) and PE on BI and ATT, respectively, was statistically not significant; FC exerted a positive influence on EE. Further, ATT was an important factor in creating BI as well as for actual usage (AU) of blended technology. The impact of BI on AU was also positive and significant. Practical Implications : The present study made an important contribution to the extant literature by proposing a modified framework for identifying the students’ BI and actual use of blended learning. The study was expected to provide useful insights into the formulation, promotion, and implementation of blended learning in educational institutions in India. In light of the ongoing advancements in technology, it was imperative to proactively foresee and effectively manage the issues that may arise concerning its integration within the field of education. This research would facilitate institutions in anticipation of forthcoming transformations within the educational domain. Originality : The originality of this study resides in its focus on how two mediators—ease of use and usefulness—played a pivotal role in changing students’ perceptions of blended learning. Notably, while social influence and performance expectations had no statistically significant effect on BI and ATT, respectively, enabling situations had a favorable effect on effort expectations.